2015
DOI: 10.3109/14767058.2015.1012065
|View full text |Cite
|
Sign up to set email alerts
|

Re-laparotomy following cesarean delivery – risk factors and outcomes

Abstract: Risk factors for re-laparotomy following CD should be identified, thus enabling more intensified monitoring of patients considered at risk for this complication. When intra-peritoneal bleeding following CD is suspected, conservative management has a high failure rate and should be reserved for a selected group of stable patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
4
7
0
Order By: Relevance
“…Rates of composite adverse maternal outcome according to number of CD performed and supervised by an attending obstetrician. 32 The rates of maternal complications of the CDs that are reported in this study are consistent with previous major publications: urinary and gastrointestinal tract injuries (0.18e0.48%), 24 blood transfusion (3.2%), 33 relaparotomy (0.23e0.4%), [34][35][36] readmission to hospital (1.8%), 23 and a composite of selected maternal adverse outcomes (19.6-21.7%). 24 Our study strengths include the large number of CDs and consistent method of real time data collection that was gleaned from electronic medical record.…”
Section: Composite Adverse Maternal Outcome By Obstetrician Annual Cesupporting
confidence: 90%
“…Rates of composite adverse maternal outcome according to number of CD performed and supervised by an attending obstetrician. 32 The rates of maternal complications of the CDs that are reported in this study are consistent with previous major publications: urinary and gastrointestinal tract injuries (0.18e0.48%), 24 blood transfusion (3.2%), 33 relaparotomy (0.23e0.4%), [34][35][36] readmission to hospital (1.8%), 23 and a composite of selected maternal adverse outcomes (19.6-21.7%). 24 Our study strengths include the large number of CDs and consistent method of real time data collection that was gleaned from electronic medical record.…”
Section: Composite Adverse Maternal Outcome By Obstetrician Annual Cesupporting
confidence: 90%
“…31 Furthermore, it seems that major obstetric hemorrhage occurs more frequently in women operated by junior as compared to senior obstetricians (19.6%, 164/835 vs. 13.1%, 153/1166). 32 The rates of maternal complications of CD reported in this study are consistent with previous major publications: urinary and gastrointestinal tract injuries 0.18-0.48%, 24 blood transfusion 3.2%, 33 re-laparotomy 0.23-0.4%, [34][35][36] readmission to hospital 1.8%, 23 and a composite of selected maternal adverse outcomes 19.6-21.7%. 24…”
Section: Commentsupporting
confidence: 89%
“…The rate of laparotomy after cesarean section in women with SAMM in the Netherlands (0.3%) appears relatively low compared to the literature (0.2-0.9%) [ 2 11 ]. Since laparotomy after vaginal birth has not been studied before, the incidence we found for laparotomy following vaginal birth cannot be compared to other studies.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies only address ‘re-laparotomy’ after cesarean section. Reported incidence rates of ‘re-laparotomy’ are low, varying between 0.2 and 0.9% [ 2 11 ]. Although data on laparotomy after vaginal birth are not reported, it has been suggested that the incidence of laparotomy may be higher after cesarean section, since operative birth is associated with a higher risk of maternal morbidity and mortality [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%